Left Ventricular Pseudoaneurysms In A Young Patient: A Case Report - Koirala, B (Nepalese Heart Journal, 2006)
Left ventricular aneurysm occurs most commonly as a consequence of myocardial Infarction. Congenital Left Ventricular aneurysms occurs rarely as diverticuli of the apex, as a part of a syndrome of congenital defects or following myocardial infarction in children with anomalous origin of coronary arteries, Post-traumatic left ventricular ancurysms are also reported in literature. Chronic infections like tuberculosis with arteritis is also reported as one of the causative factor. Here we report a case of such left ventricular pseudoaneurysms in a young patient probably ischemic in origin. The patient underwent surgery with favorable outcome.